Can you calculate that?

Algebra Level 2

Give positive numbers a a , b b , and c c are such that a b + b c + c a + a b c = 4 ab+bc+ca+abc=4 , what is the value of:

1 a + 2 + 1 b + 2 + 1 c + 2 ? \dfrac{1}{a+2}+\dfrac{1}{b+2}+\dfrac{1}{c+2}?


The answer is 1.0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Mark Hennings
Jun 4, 2019

Note that a , b , c a,b,c are the roots of the equation f ( X ) = 0 f(X) = 0 , where f ( X ) = ( X a ) ( X b ) ( X c ) = X 3 u X 2 + ( 4 v ) X v f(X) \; = \; (X-a)(X-b)(X-c) \; = \; X^3 - uX^2 + (4-v)X - v for some constants u , v u,v . But then ( 2 + a ) 1 + ( 2 + b ) 1 + ( 2 + c ) 1 = ( 2 + b ) ( 2 + c ) + ( 2 + a ) ( 2 + c ) + ( 2 + a ) ( 2 + b ) ( 2 + a ) ( 2 + b ) ( 2 + c ) = f ( 2 ) f ( 2 ) = 12 + 4 u + 4 v 8 4 u 8 + 2 v v = 16 + 4 u v 16 4 u + v = 1 \begin{aligned}(2+a)^{-1} + (2+b)^{-1} + (2+c)^{-1} & = \; \frac{(2+b)(2+c) + (2+a)(2+c) + (2+a)(2+b)}{(2+a)(2+b)(2+c)} \\ & = \; -\frac{f'(-2)}{f(-2)} \; = \; -\frac{12 + 4u + 4-v}{-8-4u-8 + 2v-v} \; = \; -\frac{16+4u-v}{-16-4u+v} \; = \; \boxed{1} \end{aligned}

Oh wow, this is a real beauty! I'm printing and laminating this solution. Thank you.

Pi Han Goh - 2 years ago

Awesome ; can you try this https://brilliant.org/problems/prove-this-looks-easy-huh/

Syed Hamza Khalid - 2 years ago
Linkin Duck
Jun 4, 2019

After reviewing the above solutions, I give an unnatural and tricky explanation here:

Because: 1 a + 2 + 1 b + 2 + 1 c + 2 1 = a b + b a + c a + a b c 4 ( a + 2 ) ( b + 2 ) ( c + 2 ) = 0 , \frac{1}{a+2}+\frac{1}{b+2}+\frac{1}{c+2}-1=-\frac{ab+ba+ca+abc-4}{\left ( a+2 \right )\left ( b+2 \right )\left ( c+2 \right )}=0,

So, 1 a + 2 + 1 b + 2 + 1 c + 2 = 1. \frac{1}{a+2}+\frac{1}{b+2}+\frac{1}{c+2}=1.

Your method works whenever the answer is known...

Mr. India - 2 years ago

You can actually know the answer for the problems. ab+bc+ac+abc=4 So let a=b=c=1 Therefore 1/a+2 + 1/b+2 + 1/c+2 = 1 So we can use this solution p/s: Chào chú cháu VN. 12 tuổi

Lê Nhật Khôi - 2 years ago

Log in to reply

Yes, you can rely on that trick to get the right answer without a solution. Nice to know you, Nhật Khôi :)

Linkin Duck - 1 year, 11 months ago

Solve a b c + a b + a c + b c = 4 a\, b\, c+a\, b+a\, c+b\, c=4 for a a give a 4 b c b c + b + c a\to \frac{4-b c}{b c+b+c} .

Substitute into 1 a + 2 + 1 b + 2 + 1 c + 2 \frac{1}{a+2}+\frac{1}{b+2}+\frac{1}{c+2} that value for a a gives 1 4 b c b c + b + c + 2 + 1 b + 2 + 1 c + 2 \frac{1}{\frac{4-b c}{b c+b+c}+2}+\frac{1}{b+2}+\frac{1}{c+2} .

Combining the terms into a single fraction gives 1 1 .

The restriction to positive reals is not necessary. It works even with C \mathbb{C} . One does need to avoid a, b or c equaling -2.

Edwin Gray
Jun 6, 2019

Clearly, the given equation is satisfied by a = b = c = 1, by inspection. Ergo, 1/(a + 2) + 1/(b + 2) + 1/(c + 2) = 1/3 + 1/3 + 1/3 = 1.

Pi Han Goh
Jun 5, 2019

Let S n S_n denote the n th n^\text{th} symmetric sum of a , b , c a,b,c . Denote S 1 = u , S 2 = v S_1 = u, S_2 = v . By Vieta's formula, the polynomial f ( x ) : = x 3 u x 2 + v x ( 4 v ) f(x) := x^3 - ux^2 + vx - (4-v) has roots a , b , c a,b,c . Similarly, f ( x 2 ) = 0 f(x-2) = 0 has roots a + 2 , b + 2 , c + 2 a + 2, b+2, c+2 . Since g ( x ) : = f ( x 2 ) = x 3 + x 2 ( u 6 ) + x ( 12 + 4 u + v ) + ( 4 u v 12 ) , g(x):= f(x-2) = x^3 + x^2 ( -u - 6) + x(12+ 4u + v) + (-4u - v - 12), then we know that x 3 g ( 1 x ) = 0 x^3 \cdot g\left(\frac 1x \right) = 0 has roots 1 a + 2 , 1 b + 2 , 1 c + 2 \frac1{a+2} , \frac1{b+2} , \frac1{c+2} . x 3 g ( 1 x ) = ( 4 u v 12 ) x 3 + x 2 ( 12 + 4 u + v ) + x ( u 6 ) + 1 x^3 \cdot g\left(\frac 1x \right) = (-4u - v - 12)x^3 + x^2 (12+ 4u + v) + x (-u - 6) + 1 By Vieta's, the expression in question is equal to 12 + 4 u + v 4 u v 12 = 1 - \frac{ 12+ 4u + v}{-4u - v - 12} = \boxed1 .


Antisolution: We know that a = b = c = 1 a=b=c=1 satisfy the given constraint. Substitute these values into the expression in question, and we have our answer!

Yup......I solved this using the method of your Antisolution!!!!

Aaghaz Mahajan - 2 years ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...